Variation in the pH of faeces in disease. Issue 4 (April 1970) - Madanagopalan, N.; Nadar, S. Arumugan; Subramaniam, R.
Abstract : Although it is highly unlikely that a disease can be definitively diagnosed from a study of the p H of the faeces alone, the present study has helped to dispel the past belief that the p H of faeces in acute amoebic dysentery is more likely to be acidic. Culture for other pathogenic organisms has not been done in the present series of cases, but the chances of the coincidence of bacillary dysentery in this group would probably not have been significant. Further, in the past a simple litmus paper test was suggested to differentiate an amoebic dysentery from a bacillary dysentery, a procedure which can no longer hold good.